Aleksandrov reflection for extrinsic geometric flows of Euclidean hypersurfaces - Chow Bennett (Advanced Nonlinear Studies, 2023)
We survey some ideas regarding the application of the Aleksandrov reflection method in partial differential equation to extrinsic geometric flows of Euclidean hypersurfaces. In this survey, we mention some related and important recent developments of others on the convergence of noncontracting flows and construction and classification of ancient flows.